The Success of Final Restoration in Indirect Pulp Capping on Oral Health-Related Quality of Life - Sartika Puspita; Regia Aristiyanto; Laelia Dwi Anggraini; Hasna Nabilah (Universitas Muhammadiyah Yogyakarta, 2023)
Quality of life can be affected by oral health. Final restoration in indirect pulp capping treatment can be a clinical assessment to determine the success of vital pulp treatment. Therefore, we intended to examine whether the success of the final restoration of the indirect pulp capping affected the oral health-related quality of life (OHRQoL). The study aims to determine the effect of the final restoration type in indirect pulp capping treatment on oral health and quality of life at the Dental Hospital of Universitas Muhammadiyah Yogyakarta (UMY). This study is analytically observational with a cross-sectional design, univariate analysis for frequency distribution, simple linear regression analysis, and bivariate analysis in the form of Spearman correlation to identify the relationship between the success of the final restoration type of the indirect pulp capping with OHRQoL. The respondents comprised 11 males (47.8%) and 12 females (52.2%). The capping material used was Ca(OH)2, Dycal (60.9%), Glass ionomer cements (GIC) (39.1%) and the final restoration type consisting of composite resin (73%) and onlay or inlay (26.1%). There was no significant effect of the final restoration type on OHRQoL, with a significant value of the Spearman analysis of 0.221 (p0.05), a correlation coefficient value of 0.265 and the significant value of the simple linear regression analysis of 0.221 (p0.05). Conclusion: The success of the final restoration type in indirect pulp capping treatment did not affect the oral health-related quality of life.